DIAGNOSTIC VALUE OF ARTHROSCOPY IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS - I. A. Chikova; V. V. Avramenko; O. I. Krasnogorskaya; R. A. Nasyrov; O. V. Kalashnikova; I. O. Kuznetsov; V. G. Chasnyk (Travmatologiâ i Ortopediâ Rossii, 2011)
29 children with monoarthiritis were included in our study. Besides routine clinical and laboratorial examination, knee arthroscopy with synovial biopsy was performed in all patients. Visual examination of synovial hyperplasia and hyperemia and microscopic examination was performed. Patients were divided into 2 groups with primary and secondary (associated with joint traumatic damage) synovitis. Patients with primary synovitis had significantly lower disease onset age, lower hemoglobin level and higher ESR and CRP and disease duration compare with secondary synovitis group. Intensive and very intensive type of synovial hyperplasia more frequently in first group, in second group more frequently mild and moderate type of synovial hyperplasia occurred. Correlation between synovial hyperplasia and hyperemia has been revealed (r=0,72, p<0,000), between hyperplasia and type of hyperplasia (r=-0,55, p<0,000), and between hyperplasia and arthritis course (r=0,42, p=0,04) was noted in primary synovitis and no any correlation in secondary synovitis. Hyperplasia stage correlated with progressive disease course (r=0,44, p<0,05) and degree with X-ray stage (r=0,48, p<0,05) in primary sinovitis. Conclusions: arthroscopy with synovial biopsy has been suggested in children with chronic monoarthritis without inflammatory activity.